Responses to Systemic Nitrogen Signaling in Arabidopsis Roots Involve trans-Zeatin in Shoots - Poitout, Arthur; Crabos, Amandine; Petřík, Ivan; Novák, Ondrej; Krouk, Gabriel; Lacombe, Benoît; Ruffel, Sandrine (The Plant cell, 2018)
Plants face temporal and spatial variation in nitrogen (N) availability. This includes heterogeneity in soil nitrate (NO3-) content. To overcome these constraints, plants modify their gene expression and physiological processes to optimize N acquisition. This plasticity relies on a complex long-distance root-shoot-root signaling network that remains poorly understood. We previously showed that cytokinin (CK) biosynthesis is required to trigger systemic N signaling. Here, we performed split-root experiments and used a combination of CK-related mutant analyses, hormone profiling, transcriptomic analysis, NO3- uptake assays, and root growth measurements to gain insight into systemic N signaling in Arabidopsis thaliana By comparing wild-type plants and mutants affected in CK biosynthesis and ABCG14-dependent root-to-shoot translocation of CK, we revealed an important role for active trans-zeatin (tZ) in systemic N signaling. Both rapid sentinel gene regulation and long-term functional acclimation to heterogeneous NO3- supply, including NO3- transport and root growth regulation, are likely mediated by the integration of tZ content in shoots. Furthermore, shoot transcriptome profiling revealed that glutamate/glutamine metabolism is likely a target of tZ root-to-shoot translocation, prompting an interesting hypothesis regarding shoot-to-root communication. Finally, this study highlights tZ-independent pathways regulating gene expression in shoots as well as NO3- uptake activity in response to total N deprivation.
Keywords: regulace genové exprese u rostlin; proteiny huseníčku; dusík; výhonky rostlin; Plant Shoots; signální transdukce; Arabidopsis Proteins; Nitrogen; Zeatin; zeatin; Gene Expression Regulation, Plant; Arabidopsis; Plant Proteins; rostlinné proteiny; Signal Transduction